(3GdeLGdS GdMSjfjIs - (3YHGS Bd MGLj Ydj GdSQGLs ((3HNW GdeDdas)
(3ChdgG (B:s
(3dTjN GdNWHGA hGdPGcQjf GdTjN cGXe SHJj GdfLaj aj QKGA GdMSjf(B... (3eLdS aj GdgGPd(B...s
(3BNQgG (B:s
(3hbGe CejQ GdeDefjf jfGOj(B: (3jG eMeOGg jG QShd Gddg aj Cj hGO CfJ edbG(B... (3hjfGOj jG hdOGg jG MSjfGg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs